Patients who leave the Emergency Department without being seen. Has COVID-19 affected this phenomenon? - Giusti, Gian Domenico; Cozzolino, Maria Rosaria; Gili, Alessio; Ceccagnoli, Andrea; Ceccarelli, Monia; Groff, Paolo; Ramacciati, Nicola (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Patients who present to an Emergency Department (ED) and leave without being seen by a physician represent a safety concern because they may become severely ill and experience adverse events as a result of lacking or delayed ED treatment. Prior to the COVID-19 outbreak, the increasing number of patients accessing care through the ED in Italy and throughout the world has had implications for health policies. Methods: A retrospective cohort study that included all ED visits from 1st January 2013 to 31st December 2018 in the Perugia University Hospital has been carried out. Results: During the 5 years investigated 26,344 out of 300,372 (8.77%) patients who attended the ED left the triage area before being seen with an average of 439 patients per month. The same phenomenon has been analysed from February to October 2020. During these 9 months there were a total of 1,824 out of 30,990 (5.88%) patients who left the ED without being seen with an average of 202 per month. The latter value is one third lower than the one related to the period investigated prior to the COVID-19 outbreak. Conclusions: Such investigation could help to differentiate actual essential demand from non-essential demand within the ED, which could inform quality-improvement policies. Several strategies could be implemented to lower the proportion of patients who leave the department without being seen. Reorganising the activities in the ED with different paths should be implemented with the aim of reducing waiting times and in turn patients’ satisfaction.